A Metabolic Activation Mechanism of 7H-Dibenzo[c,g]carbazole via O-Quinone. Part 2: Covalent Adducts of 7H-Dibenzo[c,g]carbazole-3,4-dione with Nucleic Acid Bases and Nucleosides - Weiling, Xue; Angela, Siner; Mark, Rance; Koka, Jayasimhulu; Glenn, Talaska; David, Warshawsky (ACS Publications, 2002)
7H-Dibenzo[c,g]carbazole (DBC) is a potent multispecies, multisite carcinogen present in the environment. The metabolic activation pathways of DBC are not completely known. It is hypothesized that DBC may be metabolically activated by oxidation to the reactive Michael acceptor o-quinones, which can form stable and depurinating DNA adducts. The synthesis of DBC-3,4-dione has been previously reported by this research group. In the present article, we describe the synthesis and chemical structural elucidation of nine DBC-nucleic acid adducts produced from reactions of DBC-3,4-dione with Ade, Cyt, 2′-deoxyguanosine (dGuo), 2′- deoxycytidine (dCyd), and Guo. Adducts were isolated from reaction mixtures by HPLC and analyzed using MS including elemental compositions and collision-activated dissociation (CAD), 1H NMR, and two-dimensional chemical shift correlation spectroscopy (COSY) NMR. The adducts, 7-[3,4-dione-DBC-1-yl]-Ade, N4-[3,4-dione-DBC-1-yl]-Cyt, 5-[3,4-dione-DBC-1-yl]-Cyt, two conformational isomers of N2-[3,4-dihydroxy-DBC-1-yl]-dGuo, and two conformational isomers of N2-[3,4-dihydroxy-DBC-1-yl]-Guo, were characterized. Two adducts from reactions of DBC-3,4-dione with dCyd were identified by MS but not fully characterized by NMR due to instability of the adducts. Under similar conditions, the reactions of DBC-3,4-dione with Gua and 2′-deoxyadenosine (dAdo) did not result in an identifiable adduct. Liver DNA adducts from mice treated topically with DBC-3,4-dione (100 µg) in dimethyl sulfoxide/acetone (15/85, 100 µL) were identified with 32P-postlabeling. The major adduct chromatographically matched one of the adducts formed from livers of DBC-treated mouse (adduct 3) using identical conditions.